1999
DOI: 10.1111/j.1600-0587.1999.tb00470.x
|View full text |Cite
|
Sign up to set email alerts
|

El Niño events, precipitation patterns, and rodent outbreaks are statistically associated in semiarid Chile

Abstract: laksic, F. M. 1999. El Niiio events, precipitation patterns, and rodent outbreaks are statistically associated in .semiarid Chile. -Eeography 22: 213-218.In the last two decades, several researchers have noted rodent population outbreaks in semiarid South America, in association with unusually high precipitation that seemingly concurs with El Nifio events. To date, no studies have been conducted to determine the statistical relationships between ENSO (El Nino Southern Oscillation) events, increased precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 23 publications
7
89
0
4
Order By: Relevance
“…A correlation between cycles of abundance of small mammals and the ENSO (El Nino Southern Oscillations) phenomenon has been demonstrated in Chile [39] and New Mexico [5]. Conversely, while Parmenter et al [46] demonstrated the local importance of rainfall, they found no strong correlation between ENSO and the occurrence of human cases of plague in the USA.…”
Section: Climatic Oscillationsmentioning
confidence: 75%
“…A correlation between cycles of abundance of small mammals and the ENSO (El Nino Southern Oscillations) phenomenon has been demonstrated in Chile [39] and New Mexico [5]. Conversely, while Parmenter et al [46] demonstrated the local importance of rainfall, they found no strong correlation between ENSO and the occurrence of human cases of plague in the USA.…”
Section: Climatic Oscillationsmentioning
confidence: 75%
“…PDO and ENSO are known to impact a variety of ecological systems (Holmgren et al, 2001), including those as disparate as Pacific fisheries (Mantua et al, 1997), zooplankton species composition (Keister et al, 2011), rodent outbreaks (Lima et al, 1999), and the timing of flowering in plants in the western United States (Cayan et al, 2001). Other studies have observed significant impacts of both ENSO and PDO on butterfly populations in relation to abundance ( Vandenbosch, 2003) and the size of migration (Srygley et al, 2010) for single species.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we may suggest that slowly growing species such as mammals (Leirs et al 1997;Post et al 1997;Grenfell et al 1998;Lima et al 1999), ¢sh (Friedland et al 1993Dippner 1997) and birds (Forchhammer et al 1998) are likely to respond to climatic variability in a straightforward way, whereas rapidly multiplying organisms, usually small-bodied invertebrates and micro-organisms, should predominantly show weaker correlations with environmental forces (but see Fromentin & Planque 1996;Kro« ncke et al 1998;Reid et al 1998;Tunberg & Nelson 1998;Belgrano et al 1999). However, it is possible that many rapidly multiplying organisms may have a relatively weak ability for bu¡ering environmental changes due to, for example, a shorter life span, smaller body size and limited control of movement.…”
Section: Discussionmentioning
confidence: 99%